2017
DOI: 10.1038/s41598-017-13320-4
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Drug Containing Core-Shell Nanoparticles for Lung Cancer Therapy

Abstract: Late-stage diagnosis of lung cancer occurs ~95% of the time due to late manifestation of its symptoms, necessitating rigorous treatment following diagnosis. Existing treatment methods are limited by lack of specificity, systemic toxicity, temporary remission, and radio-resistance in lung cancer cells. In this research, we have developed a folate receptor-targeting multifunctional dual drug-loaded nanoparticle (MDNP) containing a poly(N-isopropylacrylamide)-carboxymethyl chitosan shell and poly lactic-co-glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 76 publications
3
53
1
Order By: Relevance
“…Histopathology of tissues from animals treated with nondrug loaded MDNPs showed no signs of toxicity, highlighting again the safety of the carrier. Altogether, these results highlight the synergistic effect of combined chemotherapy and radiation for lung cancer treatment alongside improved localization through the addition of a targeting moiety on the MDNP surface (Menon et al, ).…”
Section: Inhalable Therapeutics For Lung Cancermentioning
confidence: 82%
“…Histopathology of tissues from animals treated with nondrug loaded MDNPs showed no signs of toxicity, highlighting again the safety of the carrier. Altogether, these results highlight the synergistic effect of combined chemotherapy and radiation for lung cancer treatment alongside improved localization through the addition of a targeting moiety on the MDNP surface (Menon et al, ).…”
Section: Inhalable Therapeutics For Lung Cancermentioning
confidence: 82%
“…Gold NPs have been examined for imaging and radiotherapy of Tu-2449 brain tumor model in mice, [1] while nanocomposite containing poly(N-isopropylacrylamide)-carboxymethyl chitosan shell and polylactic-co-glycolic acid core have been tested as drug carriers for the treatment of H460 lung tumor model in mice. [2] However, owing to reports on the adverse effects of NPs on the environment and human health, their potential toxicity has become a public concern. [3,4] It was recently reported that silica, gold, and titanium dioxide NPs could accelerate the migration of breast cancer cells in animal models and promote their invasion into the blood circulation by inducing endothelial leakiness.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, magnetic nanoparticles (MNPs) have attracted considerable attention due to their potential application in the pharmaceutical and medicine fields such as magnetic hyperthermia therapy (MHT) 1,2 , drug delivery systems [3][4][5] , magnetic resonance imaging (MRI) 6,7 , gene therapy 8 , cell labeling 9 , and immunoassay 10 .…”
mentioning
confidence: 99%